Lefty Kreh's ultimate guide to fly fishing: everything anglers need to know by the world's foremost fly-fishing expert - Kreh, Lefty (Guilford, CT The Lyons Press, 2003)
Memorial for Lionel and Viola Cyr from Jim and Donna Young 8/05
Keywords: Fly fishing; Flies -- Artificial